Psycho-emotional state of students during COVID-19 pandemic self-isolation period in the context of socio-demographic factors - Belasheva, Irina V.; Gapich, Aleksandr E.; Yesayan, Marine L.; Polshakova, Irina N.; Soloveva, Evgeniia V. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
Psycho-emotional state of youth in the COVID-19 pandemic can become an indicator of various positive or negative social transformations and trends. The purpose of the study is to determine the influence of socio-demographic factors (gender, age, year of study, the direction of professional training at university, combining study and work, living in a rural area or a city, in a private house or an apartment, with parents or independently) in conditions of self-isolation on assessment of the main components of the psycho-emotional state of the students: well-being, activity, and mood. We used the method of rapid well-being, activity, and mood assessment. The test was conducted online; the relevant materials were posted on eCampus of North Caucasus Federal University educational portal. The research results analysis was based on Kruskal Wallice H-test, the primary frequency analysis, analysis of average scale values and standard deviations for the comparison groups. The study was conducted from April 13 to May 22, 2020, and involved 1,173 students aged 17 to 36 years, enrolled in 1-5 years. The study suggests that the psycho-emotional state of students in the self-isolation period depends on their age: the younger the students are, the more likely they are to experience fatigue and decline in well-being, activity, mood. The study provided new data on the features of integrated assessments of students’ well-being, activity, and mood in conditions of forced self-isolation due to the COVID-19 pandemic.